Molecular Cloning of Cellulose Synthase Gene, SpCesA1 from Developing Xylem of Shorea parvifolia spp. parvifolia - Lau, E.T; Ho Wei, Seng; Julaihi, Abdullah (Asian Network for Scientific Information, 2009)
This study reported the isolation and in silico characterization of full-length cellulose synthase ( CesA ) cDNA from Shorea parvifolia spp. parvifolia , an important tropical hardwood tree species. Cellulose synthase (CesA) is a member of processive glycosyltransferases that involved in cellulose biosynthesis of plants. The full-length of SpCesA1 cDNA with size 3308 and 3120 bp open reading frames encoding a 1040 amino acid was isolated using RT-PCR and RACE-PCR approaches. The predicted SpCesA1 protein contained N-terminal cysteine rich zinc binding domain, 7 putative transmembrane helices (TMH), 4 U-motifs that contain a signature D, D, D, QxxRW motif, an alternating conserved region (CR-P) and 2 hypervariable regions (HVR). These entire shared domain structures suggest the functional role of SpCesA1 is involved in cellulose biosynthesis in secondary vascular tissues of S. parvifolia spp. parvifolia . Sequence comparison also revealed the high similarity (87%) among SpCesA1 and PtrCesA2 of Populus tremuloides . This further implies the involvement of SpCesA1 in catalyzes the cellulose biosynthesis of secondary cell wall rather than primary cell wall. Thus, identification of new CesA genes from tropical tree genomes is essential for enhancing knowledge of cellulose biosynthesis in trees that has many fundamental and commercial implications.